(untitled) (Research, Society and Development, 2020)
The objective of this study was to conduct a survey to assess the deposit of patents for these products in the database of the National Institute of Industrial Property (INPI), identifying dressings deposited in the patent base in Brazil in the last 10 years, and verifying which depositors with greater patent registration and distribution according to the International Patent Classification. The research took place through the prospecting of patents in the INPI database comprised in the years 2009-2018. 187 patent filings were found and after exclusion of duplicate patents, resulted in 55 applications. The deposits were classified according to the country, company, universities and independent depositors, which companies have a higher number of patent deposits related to dressings. In the first instance, they were separated as to the International Patent Classification (IPC), presenting more results regarding the Sterilization and disinfection of the air, material for dressings and surgical articles, and then regarding the presentation of the dressings, with the greatest record being the adhesives . It is concluded with the referred study, that foreign companies are the ones that have more patent deposits. In Brazil, it was observed that individuals and universities invest more in research. In addition, it was observed that there was a decrease in documents deposited over the years, which can be attributed to the global financial crisis that affects investments in research.